2010
DOI: 10.1007/s10120-010-0554-3
|View full text |Cite
|
Sign up to set email alerts
|

High preoperative neutrophil-lymphocyte ratio predicts poor survival in patients with gastric cancer

Abstract: Background. The neutrophil-lymphocyte ratio (NLR) refl ects infl ammatory status. An elevated NLR has been reported to be a prognostic indicator in some malignant tumors. The aim of this study was to evaluate the clinical signifi cance of the preoperative NLR in patients with primary gastric cancer. Results. The 5-year survival of patients with a high NLR was signifi cantly worse than that of patients with a low NLR (57% vs 82%, P < 0.001). Univariate and multivariate analyses of clinicopathological factors af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
281
4
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 341 publications
(316 citation statements)
references
References 23 publications
18
281
4
7
Order By: Relevance
“…In addition, NLR showed a significant relationship with both PFS and OS in multivariate analysis. Similar to our findings, previous studies also showed that high baseline NLR predicts poor survival in patients with operable gastric cancer [10,11,16]. These studies indicated that NLR could be a simple and reliable prognostic factor for risk stratification and might provide better treatment allocation in gastric cancer.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In addition, NLR showed a significant relationship with both PFS and OS in multivariate analysis. Similar to our findings, previous studies also showed that high baseline NLR predicts poor survival in patients with operable gastric cancer [10,11,16]. These studies indicated that NLR could be a simple and reliable prognostic factor for risk stratification and might provide better treatment allocation in gastric cancer.…”
Section: Discussionsupporting
confidence: 91%
“…Although several studies have shown a relationship between NLR and stomach cancer prognosis [10,11,15,16], previous studies have mainly focused on postoperative survival in operable AGC patients rather than metastatic AGC patients. Furthermore, there are no reports on the relationship between NLR and therapeutic response in gastric cancer, even though prediction of chemotherapeutic response in metastatic AGC patients is clinically important.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The preoperative NLR reflects inflammation status, and increases number of neutrophils and/or decreased number of lymphocytes may suppress lymphokine-activated killer cells, thereby increasing the propensity of metastasis. 11) Although the prognostic significance of the preoperative NLR was not found in patients with pulmonary adenocarcinoma, further examination should be followed.…”
Section: Discussionmentioning
confidence: 99%
“…Even patients who present in the most favorable condition and who undergo curative surgical resection often die of recurrent disease (Duncavage et al, 2010;Dozois et al, 2011). Although preoperative tumor staging is useful to select the appropriate therapeutic strategy for GC patients, clinical tumor staging alone cannot predict patients' prognosis (Shimada et al, 2010;Cao et al, 2011;Feng et al, 2011). It has been reported that some immune-related biomarkers for diagnosis/prognosis and therapy monitoring of GC patients (Aburatani 2005;Tan et al, 2009).…”
Section: Introductionmentioning
confidence: 99%